Foot Care Knowledge and Practice among Diabetic Patients Attending Primary Health Care Centers in Jeddah City - Mahdi A. Qadi,; Hasan A. Alzahrani, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Diabetics knowledge and awareness on foot care are usually associated with less foot complications and better diabetic foot condition. A cross-sectional study to assess patients foot care knowledge and practice was designed. A questionnaire to assess foot care knowledge and practices, and other related variables was conveyed through interviewing 747 diabetic patients in 7 representative primary health care centers in Jeddah city. A lower level of foot care knowledge than the optimum was noticed, particularly in daily observation to detect ulcers, and the selection of footwear suitable for diabetic patients. The weakness was encountered in the foot care practices such as using mirror for foot checkup and practices related to footwear. The practice score was significantly lower in patients with lower educational level. About two-thirds (66.5%) of the patients reported having one or more diabetic complications and 45.4% reported peripheral neuropathy. Findings indicate the need for starting a well organized and structured educational program designed for foot care in diabetics. Hence, an improved and better continuous program of periodic screens in high risk patients as to prevent diabetic foot problems and complications.